Responsabilidad empresarial y sustentabilidad turística: estudio de caso en la costa veracruzana - Wojtarowski Leal, Astrid (2025)
This study explores the socio-environmental challenges of Playa de Chachalacas, Veracruz, through the perspective of hotel sector stakeholders and their role in addressing local issues via Corporate Social Responsibility (CSR) practices. Using a qualitative, participatory approach, the research employed tools such as SWOT analysis, problem and objective trees, and targeted workshops to promote dialogue, critical reflection, and collaborative solution-building. Six hotel representatives participated as the core group, reflecting a key segment of the local tourism sector. Results show that participants recognize major socio-environmental problems, propose mitigation strategies, and value strengthening relationships with other community actors, particularly restaurateurs. The findings highlight the potential for hotel businesses to play an active role in local socio-environmental management, fostering intersectoral cooperation and contributing to the protection of ecosystems in the area.